Perceptions of fairness in common-pool resource access: farmer responses to new agricultural water use restrictions in Idaho. Issue 4 (2nd October 2019) - Running, Katrina; Burnham, Morey; Du Bray, Margaret V.
ABSTRACT: This study examines farmers' perceptions of fairness regarding an agricultural water use policy change in Idaho: the 2015 settlement agreement, a compromise between ground- and surface water farmers in Idaho's Eastern Snake Plain Aquifer (ESPA) that requires reductions in groundwater withdrawals of about 13% for all groundwater farmers. We characterize the agreement as an attempt to solve a common-pool resource social dilemma and draw on Elinor Ostrom's seven 'design principles' as a conceptual framework. Using data from 43 interviews and 265 mail surveys, we find a split between farmers who grudgingly accept the agreement as necessary to keep the region's agricultural productivity sustainable, and those who consider it unnecessary, unfair, or even illegal. A belief in the importance of protecting groundwater resources and support for local control was cited by farmers backing the agreement, whereas dissenting farmers believed outside interests had exerted too much influence throughout the negotiation process and generally mistrusted the state's groundwater data. Given that residents of the American West are likely to continue having to address declining water availability in the future due to climate change, our findings can help policymakers design effective and equitable water policies in a way that advances rural environmental justice.